Hak Konstitusional: Politik Hukum Kebebasan Beragama di Indonesia - Cristiana, Maya (Fakultas Hukum Universitas Bangka Belitung, 2022)
The Constitutional Court which aims to uphold and protect the constitutional rights of citizens and the protection of human rights. One of them is the right to freedom of religion which is guaranteed by the constitution and several regulations on human rights. The substance of the 1945 Constitution article 28I paragraph (1) explains that the right to religion is absolute for every individual, so it should apply universally and non-discriminatory. In the midst of rampant violence in the name of religion, there has been a judicial review of Law No.1/PNPS/1965 concerning the Prevention of Abuse and/or Blasphemy of Religion. This law was finally deemed contrary to the guarantee of freedom of religious rights which could not be reduced under any circumstances. Likewise, when the Constitutional Court rejected all applications. So that after the decision of the Constitutional Court the conception of Indonesian religious rights became clearer. However, those who do not agree with the decision of the Constitutional Court argue that Law No.1/PNPS/1965 is a tool to justify violence in the name of religion.